Comment on Tabet et al. Vestibular Migraine versus Méniere’s Disease: Diagnostic Utility of Electrocochleography. Audiol. Res. 2023, 13, 12–22 - Jeremy Hornibrook (Audiology Research, 2023)
I wish to comment on an aspect of the recently published article by Saliba I. et al., titled Vestibular Migraine versus Meniere’s Disease: Diagnostic Utility of Electrocochleograpy [...]